The Term Structure: Discussion - Breeden, Douglas T. (Journal of Finance, 1980)
Douglas T. Breeden, The Term Structure: Discussion, The Journal of Finance, Vol. 35, No. 2, Papers and Proceedings Thirty-Eighth Annual Meeting American Finance Association, Atlanta, Georgia, December 28-30, 1979 (May, 1980), pp. 435-438